The role of residues T248, Y249 and T422 in the function of human pregnane X receptor - Doricakova, Aneta; Novotna, Aneta; Vrzal, Radim; Pavek, Petr; Dvorak, Zdenek (Archives of toxicology, 2013)
The pregnane X receptor (PXR) is a key xenobiotic receptor that regulates the expression of numerous drug-metabolizing enzymes. Some posttranslational mechanisms modulate its transcriptional activity. Although several kinases have been shown to directly phosphorylate this receptor, little is known about phosphorylation sites of PXR. In the present work, we examined T248, Y249 and T422 putative phosphorylation sites determined based on in silico consensus kinase site prediction analysis. T248 and T422 residues are critical for the interaction of the PXR ligand-binding domain and the activation function-2 (AF2) domain. Site-directed mutagenesis analysis was performed to generate phospho-deficient and phospho-mimetic mutants. We examined transactivation activity of the PXR mutants in gene reporter assays, formation of PXRmutant/RXRα heterodimer, binding of PXR mutants to the CYP3A4 gene response element DR3 and CYP3A4 expression in HepG2 cells after expression of the mutants. We found that T248D mutant activated CYP3A4 transactivation constitutively regardless of the presence or absence of a ligand. Contrary, T248V mutant exhibited low basal and ligand-inducible transactivation capacity as compared to wild-type PXR. Dose-response analysis revealed reduced ligand-dependent transactivation potency of PXR Y249D mutant. Transactivation of the CYP3A4 promoter was abolished with T422A/D mutants. All PXR mutants formed heterodimer with RXRα at a similar level to that observed with wild-type PXR. The ability to bind to DNA in vitro was substantially decreased in case of T248D, T422D and T248V mutants. Our data thus indicate that phosphorylation of T248, Y249 and T422 residues may be critical for the both basal and ligand-activated function of PXR.
Keywords: Receptors, Steroid; Promoter Regions, Genetic; Cytochrome P-450 CYP3A; Gene Dosage; genová dávka; lidé; Mutagenesis, Site-Directed; terciární struktura proteinů; Humans; promotorové oblasti (genetika); Protein Structure, Tertiary; Binding Sites; mutageneze cílená; aktivace transkripce; Transcriptional Activation; fosforylace; buňky Hep G2; ligandy; HeLa buňky; Transfection; HeLa Cells; steroidní receptory; počítačová simulace; vazebná místa; Hep G2 Cells; Computer Simulation; cytochrom P-450 CYP3A; transfekce; Pregnane X Receptor; Phosphorylation; Ligands; pregnanový X receptor